A Scoping and Theoretical Review of Joy in Leadership in the Nonprofit Sector - Katie McIntyre; Rory Mulcahy; Wayne Graham; Meredith Lawley (Journal of Public and Nonprofit Affairs)
Effective leadership plays a critical role in the success of organizations, particularly in the nonprofit sector, with positive leader affect, and more recently joy, being one aspect of leadership that significantly influences followers. Whilst some studies of positive affect and joy in leadership have been undertaken in the nonprofit sector, lack of clarity and coherence, as well as theoretical divergence has impeded research integration. This article presents the first systematic literature review of positive affect, and more specifically joy and leadership in the nonprofit sector and systematically identifies the extent to which joy has been considered as a discrete emotion in the current nonprofit leadership literature. In addition, this article synthesises the existing nonprofit leadership literature to determine what employee outcomes joy has been shown to influence. Finally, the quality of current literature and any patterns considering joy and leadership in the nonprofit leadership literature is assessed. Future research opportunities are identified.